The influence of low‐density granite bodies on extensional basins. (5th February 2020) - Howell, Louis; Egan, Stuart; Leslie, Graham; Clarke, Stuart; Mitten, Andrew; Pringle, Jamie
Abstract : The Carboniferous northern Pennine Basin remains the type locality for the 'block and basin' tectonic framework model. It has been widely believed that during periods of tectonic extension, large low‐density bodies within the basement permit buoyant blocks to resist isostatic subsidence. However, lithosphere‐scale structural and geodynamic modelling experiments dispute this; suggesting instead that the formation of intra‐basinal highs occurs prior to lithospheric extension. In northern UK, this tectonic framework is controlled by a combination of tectonic stress, isostasy and the buoyancy forces of low‐density granite, lithospheric flexure and, importantly, the inherited structural framework. It is hoped that further study can lead to a greater appreciation of the interplay of structural and geodynamic process that control the 'block and basin' framework.